Mode Tracking of Unidirectional Carbon-Based Composite Structures Using Modified Mode Shape Vectors - Chan-Jung Kim (Crystals, 2022)
A comparison of mode shapes in isotropic structures can be efficiently performed using the modal assurance criterion (MAC) to determine the similarity between mode shape vectors. However, the unidirectional, carbon-based composite (UCBC) structure shows different dynamic characteristics according to the carbon fiber orientation, even for the same structural configuration. The MAC of a certain mode may result in a poor value for the CBC structures in the case of the existence of the distorted mode shape vector from reinforced carbon fibers. In this study, the mode tracking of the UCBC structure is proposed using the MAC value only under the modified mode shape vector to enhance the MAC value between relevant modes. Because the mode shape vectors of the UCBC structure are altered from those of the isotropic structure owing to the reinforced stiffness along the carbon fiber orientation, the modified mode shape vectors are calculated by multiplying the original vectors with the proposed modification window. The proposed method was verified for simple UCBC structures with five different carbon fiber orientations, from 0° to 90°. The UCBC structures were tracked for five modes, three bending and two torsional, and the results were discussed with reference to earlier study results.